Public Perspectives on the Role of Madrasah Tsanawiyah in Preserving Religious Values in the Digital Age - Mohammad Sabarudin; Mohamad Erihadiana; Tatang Muh Nasir; Sri Wulan; Derry Ridwan Maoshul (AL-ISHLAH: Jurnal Pendidikan, 2025)
In the digital age, adolescents face challenges in maintaining religious values due to pervasive online influences. Madrasahs, as institutions of Islamic education, are increasingly expected to uphold these values. This study investigates public perceptions of the role of Madrasah Tsanawiyah (MTs) in preserving religious principles, focusing on MTs Muslimin Citapen as a case study. A quantitative, descriptive-correlational design was employed, involving 100 randomly selected respondents from the local community. Data were collected through a structured Likert-scale questionnaire and analyzed using SPSS. Analytical methods included normality testing, Pearson correlation, and linear regression to explore the relationship between madrasah roles and public perception. The analysis revealed a strong positive correlation (r = 0.856) between the public’s perception of the madrasah’s role and its effectiveness in preserving religious values. Regression analysis showed that 84.1% of public perception variance is explained by the functional role of the madrasah. These findings emphasize the significant role of madrasahs in maintaining religious values amid digital disruption. The high correlation suggests strong community trust in the institution’s moral and spiritual guidance. Madrasahs serve as vital anchors of religious education in the digital era. However, the study’s limited scope and sample size suggest the need for broader research to enhance Islamic education’s digital integration across various regions.